Taking Care of the Future Moral Education and British Humanitarianism in South Africa - Pattenden, Oliver (Anthropological Studies of Education, 2018)
Taking Care of the Future examines the moral dimensions and transformative capacities of education and humanitarianism through an intimate portrayal of learners, volunteers, donors, and educators at a special needs school in South Africa and a partnering UK-based charity. Drawing on his professional experience of "inclusive education" in London, Oliver Pattenden investigates how systems of schooling regularly exclude and mishandle marginalized populations, particularly exploring how "street kids" and poverty-afflicted young South Africans experience these dynamics as they attempt to fashion their futures. By unpacking the ethical terrains of fundraising, voluntourism, Christian benevolence, human rights, colonial legacies, and the post-apartheid transition, Pattenden analyzes how political, economic and social aspects of intervention materialize to transform the lives of all those involved. .